IMPROVEMENT OF DISSOLUTION RATE OF INDOMETHACIN FROM FAST DISSOLVING TABLETS - Parhi, Rabinarayan (INDONESIAN JOURNAL OF PHARMACY, 2014)
In the current study Indomethacin (IM) fast dissolving tablets (FDTs) were prepared by direct compression technique in order to enhance its dissolution rate. The tablets were formulated using two different approaches; super-disintegration and efferves-cence. A combination formulation of above approaches was also developed to further improve its properties. The super-disintegrants used in the formulae were sodium starch glycolate (Primogel), cross-povidone (Kollidon) and cross-carmellose (Ac-di-sol). Sodium bicarbonate and citric acid combination was employed as effervescent ingredients. The prepared powder mixtures of IM were subjected to evaluation of various pre-compression parameters and tablets were evaluated for weight variation, dimension, hardness, friability, drug content, disintegration, wetting time, uniformity of dispersion, in vitro drug release and stability studies. The FT-IR spectra shown there are no interaction between of IM with excipient. The results of pre-compression studies indicate acceptable flow property for all the powder mixtures. The data of weight variation, dimension, hardness, friability, uniformity of dispersion and drug content studies were within the official limits. The wetting time and disintegration time decreases considerably with the increase in super-disintegrants amount. By using the combination approach, the disintegration and wetting time further decreased. In vitro dissolution studies were carried out using phosphate buffer pH 6.8 as dissolution medium for 60min and observed that formulation IF9, among super-disintegration approach, released highest percentage (97.13±2.09) of IM. In vitro drug release was highest (98.54±2.89) at 60 min for formulation IF11, when all the formulations were taken into consideration. The stability study was performed on the promised formulation IF11 at 40±2oC/ 75±5% RH for 3 months and the results indicated that there were no significant changes in aforesaid tablet properties.